New Fabry disease mutation confirms cardiomyopathy aetiology: a case report - Militaru, Sebastian (Eur Heart J Case Rep, 2018)
BACKGROUND: Aetiologic diagnosis should be a priority in cardiomyopathy patients, as some of them may benefit from efficient specific treatment. To achieve this, the best approach is to look for clinical and paraclinical ‘red flags’. CASE SUMMARY: A 55-year-old woman was referred to our centre with the diagnoses of hypertrophic cardiomyopathy (HCM), high blood pressure and dyslipidaemia. The only symptom she declared was long-term acroparesthaesia with an otherwise normal clinical exam. Lab work-up showed slightly above normal values of troponin and brain natriuretic peptide (BNP), and chronic kidney disease Stage IIIA. Both the electrocardiogram (ECG) and the echocardiography showed signs of biventricular HCM, with short PR interval on the ECG and longitudinal systolic dysfunction on the echo. Family history revealed that her son and brother had been diagnosed with Fabry disease (FD). She was then tested for FD and the results confirmed the diagnosis. Alpha-galactosidase (AGAL) levels were low and she had a severe mutation on the GLA gene (gross deletion of 3’ region of the GLA gene including coding parts of exon 7), not described before. The patient was started on specific enzyme therapy. DISCUSSION: Fabry disease is a rare X-linked disease caused by mutations on the GLA gene, which leads to low levels of AGAL and accumulation of globotriaosylceramide in the lysosomes of most tissues. Even though FD is X-linked, current medical knowledge states that most females are not mere carriers, but often present with a milder or later-onset phenotype.